The Politics of Disability: From the Disability Movement to Disability Studies - ISHIKAWA, Jun (Japanese Sociological Review, 2000)
Disability Studies finally seem to have taken off in our society. However, it is still unclear which discipline and subject it is going to take. One possible choice will be to deconstruct “disablism” with a thorough criticism conducted by post-welfare theories. However, its theoretical base is still fragile. This paper should be a kind of preliminary memorandum for the development of Disability Studies. It covers following issues : Firstly, it is argued that people with disabilities have been excluded by the labor-based allocation of goods, self-determination and self-value. Therefore, viable alternatives to this system need to be created. Secondly, the “social model of disability” developed in the field of Disability Studies in Great Britain will be briefly reviewed. Thirdly, the “cultural model of the Deaf” claimed by the Deaf Movement and Deaf Studies will also be examined. Finally, the discourse on integration versus cultural autonomy, or equality versus mutual recognition of differences as a dual choice (dichotomy) will be critiqued.